The viability of the gold dinar implementation model : a case study in Aceh - Kadri, Bedjo Santoso (Kulliyyah of Islamic Banking and Finance, International Islamic University Malaysia, 2016)
This study begins by elucidating on the status of gold dinar as money from the fiqh viewpoint. Upon establishing its legitimacy and supremacy over fiat money, the thesis then explores and addresses the numerous criticisms, issues, debates regarding gold dinar and the possibility for its implementation in the current monetary system. In this, we examine the factors and potential models for public acceptance of this new financial medium. Upon identifying the desired factors and challenges, the thesis proposes an appropriate framework for implementing the gold dinar as currency within the contemporary financial and monetary context followed by a study of its viability. The study concentrates on the sample of Aceh as an autonomous region for seeking Islamic rules implementation. Using a mix methods comprising library and field research, we examined the historical uses of gold in Islam from which we concluded that the hukm (law) of gold/silver as money is permissible, and can become compulsory (wajib) for a country, if the objectives of minting gold dinars is to protecting national independence and sovereignty. In addition, the review indicated that gold dinar as money serves more benefits while fiat money promotes numerous harms. Based on a deductive analysis, we found that gold as a measurement of value is more viable rather than the use of physical gold dinar. The study distributed 200 questionnaires showed that public acceptance of the gold dinar as money is affected by economic capability, investment capability, social capability, political capability, and Islamic value. Interestingly, economic factor is the most influential factor. Structural Equation Modelling (SEM) showed that economic capability (X1), social capability (X4), and Islamic value (X5) variables positively and significantly influence public support for adopting the gold dinar as money. The research also found that mobile payment systems based on gold as a measurement of value were a good payment system model. The model involved merchants/agents, ICT providers, clearing house, customers, and regulators. The proposed model facilitates people to conduct transactions efficiently, easily and safely by using mobile phones. The sampled scholars, businessmen, politicians, and community leaders shared the belief that the proposed model can be effectively contribute towards forming a just society that is prosperous and tranquil. However, Acts, central bank, legal tender law, government, and political support are serious challenges in implementing the proposed model. Hence, the study suggested implementation at the Cooperative level to minimize the influence of inhibiting factors.